Media Convergence and Broadcasting Practice in Nigeria: Three Broadcast Stations in Focus - Emwinromwankhoe, Osakpolor (Covenant Journal of Communication, 2020)
The debate about media convergence and its relevance in Nigeria is on-going. This study contributes to the discussion by examining how this critical construct impacts the broadcasting practice in Edo State, one of the countryâ€™s 36 political subdivisions.Â The work adopts the mixed research method to investigate 100 survey respondents and interview three discussants, which helps to generate the requisite data. Findings reveal that convergence has significantly influenced broadcasting practice, and this influence is more positive than negative. The findings also show that media convergence creates additional and better opportunities, as more distribution channels for broadcast content emerge. These developments, however, may remain unsustainable if the stakeholders do not address the identified challenges appropriately. The government of Edo State can play a leading role in addressing those challenges.